Pengaruh Variasi Tipe Sambungan Las SMAW pada Baja Karbon Rendah terhadap Uji Tarik dan Uji Impact - Azimansyah, Rafidan; Mufarida, Nely Ana; Bahri, Mokh. Hairul (Fakultas Teknik UMSU, 2025)
This study was conducted to examine the effect various fusing joint types over the tensile force and impact toughness of low carbon metal SS400 utilise Shielded Metal Arc Welding (SMAW) method. Three joint types were tested double Bevel groove, double V groove, double U groove, using 100A current and E6013 electrode with a diameter of 2,6 mm. The test were conducted at the state polytechnic of Malang. The tensile test results showed that the double Bevel joint had the highest tensil strength, with a maximum value of 11.626 Mpa. Meanwhile, the umpact test revealed the highest energy absorption at 127.468 Joules or 2.12 Joules/mm2 for the same joint type. The study concludes that the double Bevel groove joint provides the best mechanical performance for SS400 steel, making it the most recommended option for applications requiring high resistance to tensil and impact loads.